2021
DOI: 10.34172/jrhs.2021.44
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intensive Care Unit Admission among Hospitalized COVID-19 Patients in a Large University Hospital in Tehran, Iran

Abstract: Background: The rapid increase in the spread of COVID-19 and the numbers of infected patients worldwide has highlighted the need for intensive care unit (ICU) beds and more advanced therapy. This need is more urgent in resource-constrained settings. The present study aimed to identify the predictors of ICU admission among hospitalized COVID-19 patients. Study design: The current study was conducted based on a retrospective cohort design. Methods: The participants included 665 definite cases of severe acute res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
4
2
Order By: Relevance
“…Most patients belonged to the CG ( Table 1 ), as this is a study carried out in a hospital environment. Despite this, the average age did not indicate that older adults would be the most likely to present the most severe disease cases, contrary to our working hypothesis based on studies that mention advanced age as a severity factor for COVID-19 76 , 77 , 78 . This demonstrates that individuals of any age can acquire the infection and be prone to critical manifestations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Most patients belonged to the CG ( Table 1 ), as this is a study carried out in a hospital environment. Despite this, the average age did not indicate that older adults would be the most likely to present the most severe disease cases, contrary to our working hypothesis based on studies that mention advanced age as a severity factor for COVID-19 76 , 77 , 78 . This demonstrates that individuals of any age can acquire the infection and be prone to critical manifestations.…”
Section: Discussioncontrasting
confidence: 99%
“…Although there were no significant differences, our results showed that most patients were female, in disagreement with our working hypothesis and with many studies that reported a higher incidence of males, especially in the critical phase of the disease 76 , 77 , 80 , 81 . However, our observed female predominance agrees with other studies whose main focus was on post-COVID-19 82 , 83 ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reason for the difference might be related to the study population's age and the dependent variable for the analysis (mortality vs severe disease). A study conducted on 665 COVID‐19 patients in Tehran, Iran indicated that leukocytosis was one of the predictors for ICU admission 27 . Considering ICU admission as a clinical sign of disease severity, this finding was in line with the findings of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Testosterone has also been shown to have a suppressive effect on the immune system. 34 Several Lee et al, 2020 49 Gupta et al, 2021 62 Yu et al, 2020 76 You et al, 2020 14 Ma et al, 2020 75 Shi et al, 2020 72 Du et al, 2020 45 Hatami et al, 2021 63 Kim et al, 2020 15 9.08 [7.54-10. Gupta et al, 2021 62 Lee et al, 2020 49 Kim et al, 2020 15 Ma et al, 2020 75 Yu et al, 2020 76 Wei et al, 2021 32 Du et al, 2020 45 Hatami Yu et al, 2020 76 Ma et al, 2020 75 Lee et al, 2020 49 Du et al, 2020 45 Kim et al, 2020 15 Hatami et al, 2021 63 Du et al, 2020 45 Yu et al, 2020 76 Hatami et al, 2021 63 2. preclinical studies also propose that ACE2, the protein that facilitates SARS-COV-2 entry, is more frequently expressed in males compared to females, especially under pathological stress. 35 Sex differences in risk behaviours, such as smoking and drinking being higher in men, may contribute to sex differences in lung damage.…”
Section: Hypertension and Outcomesmentioning
confidence: 99%